2020
DOI: 10.1097/ccm.0000000000004447
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation for Coronavirus Disease 2019-Induced Acute Respiratory Distress Syndrome: A Multicenter Descriptive Study*

Abstract: Objectives: Severe acute respiratory distress syndrome is complicated with coronavirus disease 2019 and extracorporeal membrane oxygenation support may be necessary in severe cases. This study is to summarize the clinical features, extracorporeal membrane oxygenation characteristics, and outcomes of patients with severe acute respiratory syndrome coronavirus 2 pneumonia received extracorporeal membrane oxygenation. Design: Descriptive study from two hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
122
3
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(140 citation statements)
references
References 15 publications
9
122
3
6
Order By: Relevance
“…However, the outcome of patients treated with ECMO due to ARDS caused by COVID-19 is unclear. A recent report from China with 21 of 129 (16%) critically ill patients receiving ECMO reported a mortality of 57% ( 33 ). In our study 9% of our patients received ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…However, the outcome of patients treated with ECMO due to ARDS caused by COVID-19 is unclear. A recent report from China with 21 of 129 (16%) critically ill patients receiving ECMO reported a mortality of 57% ( 33 ). In our study 9% of our patients received ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that mortality in patients requiring ECMO for COVID-19 severe ARDS ranged from 40% to 60% ( 3 5 , 10 , 11 ). This mortality is somewhat higher than that in non-COVID-19 ARDS patients including bacterial pneumonia and severe influenza A (H1N1) ARDS ( 1 , 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…In reported cases of COVID-19, the time between the onset of symptoms and cannulation was of approximately 10–17 days ( 3 , 10 , 14 ). In addition, all reported cases of COVID-19 had a duration from invasive mechanical ventilation to ECMO of less than 7 days ( 3 , 10 , 14 ). Furthermore, Yang et al ( 3 ) suggested that in the setting of COVID-19, earlier initiation of ECMO (evaluated by the length of mechanical ventilation before ECMO initiation) might be associated with improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations